Students’ Reversible Thinking Ability in Solving Quadrilateral Problems - Tata Frarisia; Sufyani Prabawanto; Cece Kustiawan (Jurnal Pendidikan MIPA, 2024)
Students’ ability to engage in reversible thinking can enhance their problem- solving skills. Reversible thinking allows students to consider various perspectives, explore different options, and determine the best solution. Therefore, this study aims to describe students’ abilities to solve reversible thinking problems in the context of quadrilaterals, specifically rectangles. This research uses a qualitative method. The participants in this study were three junior high school students from Jambi, Indonesia, who demonstrated sufficient mathematical abilities. This study found that students could solve forward-thinking problems effectively but faced challenges with reversible thinking problems. This difficulty stems from students’ lack of familiarity with problems that require reversible thinking and their struggles with modeling mathematical scenarios from word problems. The study emphasizes the need to introduce more non-routine problems and exercises that encourage the exploration of various problem-solving approaches so that students can develop more flexible thinking skills.         Keywords: reversible thinking, mathematics education, problem-solving, non-routine problem.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp542-553